Prevalence of Gastrointestinal Endoparasites of Swamp Buffaloes (Bubalus bubalis) in Polewali Mandar - Sukoco, Hendro; Fahrodi, Deka Uli; Salmin, Salmin; Said, Nur Saidah; Marsudi, Marsudi; Gading, Besse Mahbuba We Tenri (Jurnal Medik Veteriner, 2023)
This study aimed to identify the prevalence of gastrointestinal endoparasite infections in swamp buffalo (Bubalus bubalis) in Polewali Mandar. This study was used 80 samples of buffalo feces taken from community farms in the three districts with the largest population in Polewali Mandar i.e., Tinambung, Luyo and Campalagian. The data obtained were analyzed descriptively. The results of the examination of 80 samples of buffalo feces in this study found 48 (60%) positive samples infected with gastrointestinal endoparasites. After microscopic identification, the following types of endoparasites were found with their respective prevalence levels: worms of the nematode class consisted of Strongyloides sp. (8,75%), Toxocara sp. (13,75%), Ascaris sp. (7,5%), Bunostomum sp. (11,25%), Haemonchus sp. (17,5%), Trichostrongylus sp. (36,25%), the cestode class consisted of Moniezia sp. (18,75%) and Taenia sp. (10%), Trematode class Paramphistomum sp. (13,75%). The types of protozoa found were Eimeria sp. (46,25%) and Entamoeba sp. (6,25%).